Understanding the Evolution of Smoke Mass Extinction Efficiency Using Field Campaign Measurements. Issue 18 (22nd September 2022) - Saide, Pablo E.; Thapa, Laura H.; Ye, Xinxin; Pagonis, Demetrios; Campuzano‐Jost, Pedro; Guo, Hongyu; Schuneman, Melinda L.; Jimenez, Jose‐Luis; Moore, Richard; Wiggins, Elizabeth; Winstead, Edward; Robinson, Claire; et al.
Abstract: Aerosol mass extinction efficiency (MEE) is a key aerosol property used to connect aerosol optical properties with aerosol mass concentrations. Using measurements of smoke obtained during the Fire Influence on Regional to Global Environments and Air Quality (FIREX‐AQ) campaign we find that mid‐visible smoke MEE can change by a factor of 2–3 between fresh smoke (<2 hr old) and one‐day‐old smoke. While increases in aerosol size partially explain this trend, changes in the real part of the aerosol refractive index (real(n)) are necessary to provide closure assuming Mie theory. Real(n) estimates derived from multiple days of FIREX‐AQ measurements increase with age (from 1.40 – 1.45 to 1.5–1.54 from fresh to one‐day‐old) and are found to be positively correlated with organic aerosol oxidation state and aerosol size, and negatively correlated with smoke volatility. Future laboratory, field, and modeling studies should focus on better understanding and parameterizing these relationships to fully represent smoke aging. Plain Language Summary: A common way to observe airborne particles produced by biomass burning is through aerosol optical properties, for instance, using aerosol optical depth from satellites or low‐cost sensors that measure scattered light. Since health effects are associated to aerosol mass concentrations, a conversion factor between them is needed. Here we use in‐plume measurements collected from an aircraft to show that aging processes alone can produce a factor of 2–3 change in aerosol extinction per unit of aerosol mass concentration. We also find that these changes are driven not only due to changes in aerosol size, but also due to changes in the material properties of aerosols. These results are relevant as fires are becoming more common and extreme, and thus these changes in smoke properties need to be taken into consideration in many fields of study such as assimilating satellite smoke into atmospheric composition models, satellite‐based smoke impacts on health, and corrections for low‐cost PM2.5 sensors. Key Points: Aerosol mass extinction efficiency can increase up to a factor of 2–3 after 1 day of aging Changes in both particle mean diameter and real part of the refractive index are needed to fully explain the changes Changes in the estimated real part of the refractive index are correlated to organic aerosol oxidation state, volatility, and particle size